Microsporidian Nosema bombycis secretes serine protease inhibitor to suppress host cell apoptosis via Caspase BmICE. - Maoshuang Ran; Jialing Bao; Boning Li; Yulian Shi; Wenxin Yang; Xianzhi Meng; Jie Chen; Junhong Wei; Mengxian Long; Tian Li; Chunfeng Li; Guoqing Pan; et al. (PLoS Pathogens)
Microsporidia are a group of intracellular pathogens that actively manipulate host cell biological processes to facilitate their intracellular niche. Apoptosis is an important defense mechanism by which host cell control intracellular pathogens. Microsporidia modulating host cell apoptosis has been reported previously, however the molecular mechanism is not yet clear. In this report, we describe that the microsporidia Nosema bombycis inhibits apoptosis of Bombyx mori cells through a secreted protein NbSPN14, which is a serine protease inhibitor (Serpin). An immunofluorescent assay demonstrated that upon infection with N. bombycis, NbSPN14 was initially found in the B. mori cell cytoplasm and then became enriched in the host cell nucleus. Overexpression and RNA-interference (RNAi) of NbSPN14 in B. mori' embryo cell confirmed that NbSPN14 inhibited host cells apoptosis. Immunofluorescent and Co-IP assays verified the co-localization and interaction of NbSPN14 with the BmICE, the Caspase 3 homolog in B. mori. Knocking out of BmICE or mutating the BmICE-interacting P1 site of NbSPN14, eliminated the localization of NbSPN14 into the host nucleus and prevented the apoptosis-inhibiting effect of NbSPN14, which also proved that the interaction between BmICE and NbSPN14 occurred in host cytoplasm and the NbSPN14 translocation into host cell nucleus depends on BmICE. These data elucidate that N. bombycis secretory protein NbSPN14 inhibits host cell apoptosis by directly inhibiting the Caspase protease BmICE, which provides an important insight for understanding pathogen-host interactions and a potential therapeutic target for N. bombycis proliferation.